The Role of Social Competence of Catholic Religious Education Teachers towards Student Learning Motivation: Social Competence - Ginting, Elisa Br; Lumbanbatu, Johannes Sohirimon; Simarmata, Petrus (Universitas Negeri Surabaya, 2022)
The social competence of Catholic Religious Education teachers has an influence on education because teachers as part of the community are expected to be able to establish good relations with students, colleagues, and the community. This study was conducted to analyze how the role of social competence of Catholic religious education teachers to the motivation of learning students in grade VIII A Private Junior High School Santo Xaverius 2 Kabanjahe with informants as many as 19 people consisting of: Catholic Religious Education Teachers, peers, learners and parents. This study uses a qualitative approach. The results showed that 1) behaving and acting objectively; objective teachers in assessing learning outcomes; act wisely and justly; motivators, facilitators and get along with students. 2) adapt to the environment; can respect; establish intimate relationships full of kinship and eliminate personal interests. 3) communicate effectively; have knowledge of customs both social and religious; and communicate with the local community. 4) empathetic and polite; have an image in the community, care, and manners. 5) Diligent in learning, learners are independent in doing tasks, responsible, have a passion in doing tasks and completing them on time. 6) The existence of awards in learning, getting praise, spirit, and motivation from catholic religious education teachers, 7) The existence of interesting activities in learning, able to answer questions well, complete simulations, and daily exams well, and 8) The existence of a conducive learning environment, having a clean classroom, comfortable, calm atmosphere and complete facilities.